Facile synthesis of porous carbon spheres embedded with metal nanoparticles and their applications as supercapacitor electrodes. Issue 94 (23rd September 2016) - Tan, Yuanzhong; Wong, Ka-wai; Ng, Ka Ming
Abstract : A porous carbon matrix with uniformly dispersed metal nanoparticles was synthesized using a facile template-free method. Abstract : We report a novel synthetic method to prepare porous carbon spheres embedded with metal nanoparticles (M-PCS) by hydrothermal treatment of a solution of sodium gluconate and a metal salt, followed by calcination in N2 . It is a template-free method and offers a combination of a porous structure and uniformly dispersed metal nanoparticles. As one of the potential applications, the as-prepared M-PCS possess an ultrahigh capacitance (1308.7, 1380.9 and 543.6 F g −1 for Fe-PCS, Co-PCS, and Ni-PCS, respectively at a current density of 10 A g −1 ) when applied as an electrode material for supercapacitors.